AGROTOURISM DEVELOPMENT OF MAPPING BRAND POSITIONING AND COMPETITVE LANDSCAPE: UGC (USER GENERATED CONTENT) APPROACH - Annisa Firdauzi; Agustina Shinta Hartanti Wahyuningtyas; Riyanti Isaskar (Agricultural Socio-Economics Journal, 2021)
Starting from 2009-2018 there has been an increase in the number of hotel resorts in Indonesia, so that the level of competition is higher and building a brand positioning agrotourism-based resort hotels can not only by creating regular marketing campaigns. The study used review data from online platforms tripadvisor.com. This study reveals the brand positioning of resort hotels and mapping the competitive landscape with the UGC approach to identifying the competing attributes of resort hotels in Bali. This study detects brand attributes using customer preferences as well as perceptual performance. Therefore, this study combines content analysis (UGC) and repertory grid (RGA) to answer research objectives. 13,784 customer reviews of the six best beach resort hotels in Bali are used to explore and visualize the competitive landscape. Sample determination techniques in this study using non-probability sampling approach. The findings of this study, identified the dominant agrotourism attributes in Bali are view and garden. This study detected that 66.67% of hotel resorts in Bali have asymmetric competitive model competition. Hotel resorts in Bali is mostly competing on PC1 which is a basic hotel offer. This research not only recommends competing for attributes to strengthen brand positioning in customers' minds but also competes with optimal allocation of hotel resort resources.